664.8(035) Qishloq xo'jaligi mahsulotlarini yetishtirish, saqlash qayta ishlash va oziq-ovqat texnologiyalari: IMPROVING THE TECHNOLOGY OF PRODUCTION OF FUNCTIONAL NUTRITION JUICES - Xodjiyev, Adxamjon; Choriev, Abdusattar; Raximov, Umidjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The chemical composition and useful substances of carrot and lemon juices for human life have been studied. The technology of blended juice production is investigated